Vitamin E As a Potential Interventional Treatment for Metabolic Syndrome: Evidence from Animal and Human Studies - Wong, Sok Kuan; Chin, Kok-Yong; Suhaimi, Farihah Hj; Ahmad, Fairus; Ima-Nirwana, Soelaiman (Frontiers in Pharmacology, 2017)
A constellation of medical conditions inclusive of central obesity, hyperglycemia, hypertension, and dyslipidemia is known as metabolic syndrome (MetS). The safest option in curtailing the progression of MetS is through maintaining a healthy lifestyle, which by itself, is a long-term commitment entailing much determination. A combination of pharmacological and non-pharmacological approach, as well as lifestyle modification is a more holistic alternative in the management of MetS. Vitamin E has been revealed to possess anti-oxidative, anti-inflammatory, anti-obesity, anti-hyperglycemic, anti-hypertensive and anti-hypercholesterolemic properties. The pathways regulated by vitamin E are critical in the development of MetS and its components. Therefore, we postulate that vitamin E may exert some health benefits on MetS patients. This review intends to summarize the evidence in animal and human studies on the effects of vitamin E and articulate the contrasting potential of tocopherol (TF) and tocotrienol (T3) in preventing the medical conditions associated with MetS. As a conclusion, this review suggests that vitamin E may be a promising agent for attenuating MetS.